The Current State of Interaction of International Organizations and Public Authorities in Ukraine in the Field of Public Finance - IVANOVA, Roksolana (University Scientific Notes, 2021)
The author states that Ukraine continues to implement active measures to reform public authorities, local governments, energy system, economic climate, law enforcement, social protection systems for vulnerable groups and more. The state aims to form a stable and perfect national financial system, as this is one of the main conditions for the effective development of the national economy and creating the conditions for the well-being of the population. However, the construction of an effective national financial system is impossible without its interaction with the world economy, which is characterized by the process of globalization. In addition, such modernization and reform require significant resources, which Ukraine lacks. That is why the cooperation of Ukraine with international organizations in the field of public finance comes to the fore. International financial organizations are becoming increasingly important in international economic and financial relations, as their network carries a significant share of global investment, there is a purchase and sale of currency to finance export-import operations, and so on. In addition, given the globalization processes in the world and the needs of developing countries, international financial organizations today play a key role in implementing reforms in major areas of public life, helping to minimize possible crises in national financial systems. Cooperation with international financial organizations is also an integral part of the foreign policy of our state, as well as an activist for the development of financial and economic Ukraine. Such cooperation has an impact on public financial activities, the peculiarities of the formation, distribution and use of monetary resources, as well as the organization of money circulation and financial control. The explanation of the issue of «international financial organization» should be fixed on the achievements of international science, Administrative Law and Financial Law. International financial organizations are organizations established under several states that are subjects of Public International Law and which provide financial resources to member states of international financial organizations on the terms specified in their documents. In the international steam literature, the concept of international financial organizations is also understood as such an organization, which is endowed by its members with competent activities in the monetary and financial sphere and which is more or less involved in the functioning of the international financial system.